Phenotypic diversity of bacteria in root nodules of Dalbergia ecastaphyllum (L.) Taub. (Fabaceae) - Carmen Trujillo Pacheco, Lidia Del (2021)
Many species belonging to family Fabaceae are able to establish symbiotic relationships with nitrogen-fixing bacteria. Studies developed with Dalbergia ecastaphyllum (L.) Taub., for example, have demonstrated the symbiotic potential of this species. In this sense, this study aimed to analyze the phenotypic characteristics of rhizobia isolated from D. ecastaphyllum and to identify whether these bacterial isolates are capable of establishing symbiotic relationships with Vigna unguiculata (L.) Walp. D. ecastaphyllum seeds were sown in soil samples collected in Japaratinga, Alagoas, Brazil, in three zones located at different distances from the high tide line. At 60 days after the emergence of the plants, nodulation in the roots of D. ecastaphyllum was analyzed and the bacteria were isolated. Subsequently, the phenotypic characterization of the bacteria was carried out based on some criteria (growth time, type of pH, colony color, type of mucus and amount of mucus). For the nodulation test, the species V. unguiculata was used. In total, 17 phenotypic types of bacterial isolates were identified, of which 8 are fast-growing and 9 are intermediate-growth. Regarding the type of pH, 7 phenotypes are acidic pH, 8 are neutral pH and 2 are alkaline pH. As for the coloring of the bacterial colonies, 5 are yellow, 7 white and 5 pink. It was also observed the presence of consistent and aqueous mucus in colonies from the three different areas. Only 7 bacterial phenotypic types and the commercial inoculant were efficient in the nodulation of V. unguiculata.